Sistema de ciberseguridad mediante biblioteca de código abierto en los servidores de los hospitales del IESS provincia de Manabí - Cedeño Mosquera, Cristhian Javier (2023)
This titling project focused on addressing the growing concern about cyber security in IESS hospitals in the province of Manabí. The main objective was to implement an efficient and effective cybersecurity system using an open-source library. To achieve this, an exhaustive analysis of the vulnerabilities and threats present in the hospital servers was carried out. A suitable open-source library was selected, which provided robust tools and functionalities to strengthen cyber security, potential risks were identified based on the results generated by the executed analysis tool. This library was implemented in hospital servers, adapted, and configured to guarantee the integrity and confidentiality of the information. Among the most relevant results was SSH access via empty passwords, Unconfigured grub2 bootloader password, and Unconfigured bootloader admin username in a non-default value. The corrective measures applied demonstrated a significant improvement in the security of the servers of the IESS hospitals in the province of Manabí, reducing the risk of cyber attacks, data loss, and exposure to sensitive information.